A CORPUS-BASED ANALYSIS OF CONJUNCTION IN BUSINESS ARTICLE OF Jakartaglobe.id - Laila Tanya Carolina (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
An article is one of the media to search for information and also knowledge. EFL students can read an article on a website that can be accessed from a smartphone. Online media is beneficial in finding information. In this era, many websites can be accessed to get a piece of information. Jakartaglobe.id is one of many websites. From Jakartaglobe.id students can search about lifestyle, opinion, business, news, and technology. This information can be from Indonesia or around the world. It is easy to search. Grammar is essential for some articles. In grammar, we can learn about a part of speech. In part of speech, we learn about nouns, verbs, adverbs, adjectives, pronouns, prepositions, and conjunction. This paper focuses on conjunction. The conjunctions are a word to connect some words or clauses to become a sentence. The conjunction is important to know or understand the meaning of some text. The conjunction can help to learn about the text and without misunderstanding. This paper aimed to identify what kinds of conjunctions in a business article of Jakartaglobe.id. This paper also gives information or something important for corpus linguistics. Corpus linguistics is a subject that can help EFL students to learn the English language easily. This study used a descriptive quantitative method.